'Keeper of the fire': human resource management's role in the organisational development of an employee sustainability mindset. (2018) - Nathan, Maria L.
Sustainability is "meeting the needs and demands of today without compromising the ability of future generations to meet their requirements" [Burton, (1987), p.8] Sustainable development requires that organisations' social, environmental, well-being, and economic factors are managed in balance and from short and long-term as well as external and internal perspectives organisations have been advised to yoke sustainability practice to virtually every facet of an organisation's strategic management process, including human resource management as a functional level organisational strategic unit In recent years, human resource management (HRM) has been highlighted as a key agent with which to advance the firm because it is a central internal consultant for all matters of human capital management Thusly positioned, HRM can play a critical role in engendering employee sustainability practices. The purpose of this paper is to flesh out a key, core role for HRM as 'keeper of the fire' of an employee sustainability mindset Essentials of mindset are first developed, then the sustainability mindset and its integration into HRM and employee practices is explored Finally, critical concerns and future directions for sustainable HRM practice are examined.